Differentiation BIRADS I vs II by Magnetic Induction Spectroscopy: A Potential Innovative Method to Detect Neoplasies in Breast - González-Díaz, C A; Uscanga-Carmona, M C; Ibarra-Martínez, C D; Jiménez-Fernández, M E; Lozano-Trenado, L M; Silva-Escobedo, J G; Polo-Soto, S M (Revista Mexicana de Ingenieria Biomedica, 2012)
Introduction.- Current limitations in the treatment of Breast Cancer (BC) are associated with late diagnosis of the disease. At present, there is no portable technology that allows a noninvasive diagnosis of early-stage tumors in the mammary gland. The electrical bioimpedance of neoplastic tissue is differentiable with respect to the normal tissue. We have proposed bioimpedance measurements by Magnetic Induction Spectroscopy (MIS) as a noninvasive alternative to detect neoplasia in mammary gland. Objective.- To explore the feasibility of detecting neoplasia in mammary gland through MIS and to determine whether this technique allows the discrimination of BIRADS mammographic findings I vs II. Material and Methods.- Voluntary women with mammographic findings BIRADS I and II were monitored with an experimental portable inductive spectrometer to evaluate the influence of MIS in breast tissue in the bandwidth of 0.001 to 100 MHz. MIS measurements, body temperature and anthropometric values were compared by a parametric statistical test. Results.-Small differences in the inductive phase shift at frequencies below 100 kHz are evident between BIRADS groups. A mean value comparison of inductive phase shift at each frequency through at-student test for independent samples showed statistically significant differences only at the frequency of 1.81 kHz. Discussion and Conclusion.-MIS measurements in breast tissue through the dielectric dispersion range below 100 kHz show technical feasibility to differentiate mamografical findings BIRADS I and II. Possible effects associated with temperature or instrumentation artifacts may confuse the MIS measurements. Extensive clinical studies of sensitivity and specificity to detect neoplasia in mammary gland are required to confirm the findings so far observed.